Operations management - Stevenson, William J. (McGraw-Hill, 2007)
Operations Management features the latest concepts and applications while not losing focus on the core concepts that has made this text a market leader. This approachable text supports students in applying concepts and methods by providing solved problems, examples, questions, practice problems, and cases. Students learn by doing, and the Ninth Edition continues to offer more support for 'doing Operations' than any other